2016
DOI: 10.1021/acs.orglett.6b02890
|View full text |Cite
|
Sign up to set email alerts
|

Nucleophilic Tetrafluoroethylation Employing in Situ Formed Organomagnesium Reagents

Abstract: Tetrafluoroalkyl bromides are metalated with equimolar iPrMgCl·LiCl (Turbo Grignard) to form organomagnesium compounds which are stable at low temperatures and react with various electrophiles (aldehydes, ketones, CO, cyclic sulfate and sulfamidate, N-sulfonylimines, nitrone, chlorophosphate, nonaflyl azide) to afford novel functionalized tetrafluoroethylene-containing products. Ease of operation, excellent selectivity, high nucleophilicity, and enhanced stability of the reactive species together with a broad … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…At 100 °C, 2-Zn was almost completely decomposed after being stirred for 2 h, with a recovery yield of only 8%. According to Beier’s report [ 22 23 ], tetrafluoroethylmagnesium species fully decompose within 50 min at −40 °C; CH 2 =CHCF 2 CF 2 ZnBr ( 2-Zn ) used in the present study was shown to be much more thermally stable than tetrafluoroethyllithium [ 12 , 25 ] and -magnesium species [ 22 23 ].…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…At 100 °C, 2-Zn was almost completely decomposed after being stirred for 2 h, with a recovery yield of only 8%. According to Beier’s report [ 22 23 ], tetrafluoroethylmagnesium species fully decompose within 50 min at −40 °C; CH 2 =CHCF 2 CF 2 ZnBr ( 2-Zn ) used in the present study was shown to be much more thermally stable than tetrafluoroethyllithium [ 12 , 25 ] and -magnesium species [ 22 23 ].…”
Section: Resultsmentioning
confidence: 84%
“…Gouverneur et al disclosed a Cu(I)-mediated cross-coupling reaction using ArCF 2 CF 2 SiMe 3 derivatives that produced the corresponding tetrafluoroethylenated compounds [ 21 ]. Beier’s group also described a broad range of tetrafluoroethylene compounds generated by the reductive coupling of in situ-formed RCF 2 CF 2 MgCl·LiCl with various electrophiles [ 22 23 ]. Our group revealed that commercially available 4-bromo-3,3,4,4-tetrafluorobut-1-ene ( 1 ) underwent a Cu(0)-mediated cross-coupling reaction with aromatic iodides in DMSO at 160 °C in a sealed-tube apparatus [ 24 ] or reductive couplings with various carbonyl compounds [ 25 ], leading to good yields of versatile CF 2 CF 2 -containing substances.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the structure of ArCF 2 CF 2 R, is prepared via fluorination methods, such as fluorine addition to arylacetylenes or deoxofluorination of 1,2‐dicarbonyl compounds. Recently, some new protocols to access to this formula were developed by Gouverneur, Togni, Beier, Hu, and Cho . In those reactions, ArCF 2 CF 2 Br, ArCF 2 CF 2 SiMe 3 and hypervalent iodine reagents were used as fluoroalkylated reagents.…”
Section: Figurementioning
confidence: 99%
“…We have earlier found that the metalated species are stable at this temperature and metalation times range from less than 5 min for R 1 = PhS and alkyl to half an hour or slightly longer for R 1 = imidazolyl, pyrazolyl and ArO. 32 An electrophilic azide source (tosyl or nonaflyl azide working equally well) was then added to the generated Grignard reagent and the temperature was allowed to rise to ambient temperature over a period of 3 hours. In this way, good yields of tetrafluoroethyl azides (2) were obtained with electronneutral, -withdrawing or -donating groups on the aryl ring of the aryloxy substituent (R 1 = ArO) ( Table 1).…”
mentioning
confidence: 95%
“…In the latest report, tetrafluoroethyl bromides were reacted with i-PrMgCl•LiCl to afford metalated species stable at low temperature and displaying excellent reactivity with a range of electrophiles with one example of an electrophilic azide. 32 Azides are highly valuable compounds in organic synthesissome fluoroalkyl azides are known, [33][34][35][36][37][38][39][40] including CF 3 N 3 41,42 and perfluoroalkyl analogues for which we have recently reported a new and practical synthetic method. 43 Perfluoroalkyl azides were investigated in copper(I)catalyzed azide-alkyne cycloadditon (CuAAC) [44][45][46] furnishing N-perfluoroalkyl-1,2,3-triazoles.…”
mentioning
confidence: 99%